Profile of trifluridine/tipiracil hydrochloride in the treatment of metastatic colorectal cancer: efficacy, safety, and place in therapy - Sunakawa, Yu (Onco Targets Ther, 2017)
TAS-102, with its robust survival efficacy and feasible toxicity, is one of the standard salvage-line treatments for patients with metastatic colorectal cancer (mCRC). No definitive data are available to determine which drug should be administered first during salvage-line treatment. Therefore, it is imperative that we establish the sequence of administration by considering drug toxicity profiles based on patient characteristics, such as age, performance status, comorbidities, tolerability to previous treatments, and patient preferences. The identification of predictive biomarkers in response to TAS-102 or its toxicity is urgently needed for better patient selection. Moreover, to strengthen efficacy or relieve toxicity, combinations with other agents, which could potentially emerge as standard treatment regimens, have been investigated and compared to existing active regimens for mCRC.